Synthesis, Chiral Resolution, and Absolute Configuration of Functionalized Tröger’s Base Derivatives: Part III - Jarzebski, Andreas; Bannwarth, Christoph; Tenten, Christina; Benkhäuser, Christian; Schnakenburg, Gregor; Grimme, Stefan; Lützen, Arne (Synthesis, 2015)
Eleven different derivatives of Tröger’s base were synthesized and successfully resolved by (recycling) HPLC on chiral stationary (S,S)-Whelk-O1 or CHIRALPAK IA phase on a (semi-) preparative scale or synthesized in enantiomerically pure form. The absolute configuration was determined by X-ray crystal structure analysis, comparison of the quantum chemically calculated circular dichroism spectra with the experimental spectra, or comparison of specific rotations with literature data.
Keywords: Tröger’s base; enantiomeric resolution; HPLC techniques; circular dichroism; time-dependent density functional theory